2020
DOI: 10.1002/ep.13405
|View full text |Cite
|
Sign up to set email alerts
|

Exergoeconomic analysis and optimization of reverse osmosis desalination integrated with geothermal energy

Abstract: In this research, the integrated carbon dioxide power cycle with the geothermal energy source to supply the required reverse osmosis desalination power for freshwater production is defined. The cycling power is consumed by the desalination system and sodium hypochlorite generator. Exergoeconomic analysis, and optimization are studied. Exergoeconomic analysis is shown that the desalination system, sodium hypochlorite generator, carbon dioxide turbine, and natural gas turbine have the highest rate for the sum of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(15 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Constraints have been considered in 50% of the core literature. Technically, constraints are sorted out into two groups, equality and inequality [80][81][82]. Equality constraints are those that bind the optimization to satisfy the equations.…”
Section: Constraintsmentioning
confidence: 99%
“…Constraints have been considered in 50% of the core literature. Technically, constraints are sorted out into two groups, equality and inequality [80][81][82]. Equality constraints are those that bind the optimization to satisfy the equations.…”
Section: Constraintsmentioning
confidence: 99%
“…The growing interest in moving energy generation away from petroleum fuels and toward alternative means is pulling together considerations for the utilization of renewable energy sources to help meet the global energy needs and sustainability of the environment. Thus, the previous decade has witnessed an increasing attention for understanding the roles the renewable energy sources can play in the energy adequacy and a quantum rise in research support into conversion technologies and obtainability as reported by a number of authors (Ganesan et al, 2013;Hoseinzadeh et al, 2020;Javadi et al, 2020;Mason et al, 2009;Siamak et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Baghban et al [33] did an experimental and modelling study of heat transfer performance of water-SiO2 nanofluid in quadrangular cross-section channels. Hoseinzadeh et al [34] performed exergeoeconomic, and optimization analyzes for a model for seawater desalination. Abadi et al [35] conducted a numerical and experimental study on the energy efficiency of a regenerative heat and mass exchanger by utilizing the counter-flow Maisotsenko cycle.…”
Section: Introductionmentioning
confidence: 99%